2011
DOI: 10.1080/00222895.2011.557751
|View full text |Cite
|
Sign up to set email alerts
|

Using the Movement-Related Cortical Potential to Study Motor Skill Learning

Abstract: The movement-related cortical potential (MRCP) is a low-frequency negative shift in the electroencephalographic recording that occurs about 2 s before voluntary movement production. The MRCP is thought to reflect the cortical processes involved in movement planning and movement preparation. In recent years, researchers have used this potential to investigate the processes involved in motor skill learning. Their findings indicate differences in the amplitude and onset times of the MRCP between experienced and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
65
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 31 publications
1
65
0
Order By: Relevance
“…Previous MRCP studies [24], [25], [26], [27], [28], [29], [30] have found a reduction in the BP component in skilled participants and have attributed it to smaller and more economic motor preparation in the supplementary motor areas of skilled individuals. The present study did not confirm this notion statistically; however, the results showed a similar trend for BP negativity.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Previous MRCP studies [24], [25], [26], [27], [28], [29], [30] have found a reduction in the BP component in skilled participants and have attributed it to smaller and more economic motor preparation in the supplementary motor areas of skilled individuals. The present study did not confirm this notion statistically; however, the results showed a similar trend for BP negativity.…”
Section: Discussionmentioning
confidence: 92%
“…The main findings from these studies are that expert performers show smaller amplitude and later onset MRCPs prior to task performance than their novice counterparts. This fact has been observed in groups of expert clay target [24] and pistol shooters [30], elite and novice kendo martial art performers [25], [26] and guitar players [27], [28], [29]. It has been concluded that experienced performers are able to plan and perform the task with reduced cortical activity compared to novices and that these differences can be attributed to long-term training by the expert group.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…Improvement in accuracy and latency of single-trial MRCP detection is therefore a relevant challenge. The amplitude of the MRCP is typically between 5 and 30 μV and therefore easily masked by other brain activities (Wright et al, 2011). Moreover, low frequency motion artifacts and the electrooculogram (EOG) have frequency bandwidths similar to the MRCP, but with much greater magnitudes.…”
Section: Introductionmentioning
confidence: 99%
“…The cognitive ability to assess the environment and adapt motor skills to satisfy the demands of novel movement tasks or environments (executive functioning) provides increased opportunities to explore and display mastery in a wide range of PAs (sport, dance, exercise etc. ; Seifert et al, 2011;Seifert, Button, & Davids, 2013, Wright, Holmes, & Smith, 2011.…”
Section: Deliberate Preparation -The Centrality Of Movement Skillsmentioning
confidence: 99%